Fauna de Amphipoda (Crustacea) associada à esponja Dysidea sp. em Arraial do Cabo, RJ - taxonomia e composição da comunidade - Serejo, Cristiana Silveira (1995)
During the period between July 1993 and May 1994, 50 colonies of sponges Dysidea sp. were colected at Arraial do Cabo, Rio de Janeiro, Brazil. The amphipod fauna associated with these sponges was identified and quantified, resulting in a total of 4978 specimens included in 29 species. Two new species were described and illustrated, being one of the genus Autonoe and the other of Podocerus. Gammaropsis palmata (Stebbing & Robertson, 1891) and Perioculodes cf. aequimanus (Krossmann, 1880) were found to be new records for the Western Atlantic. Fallotritella montoucheti Quitete 1971, which had been recorded earlier from the Brazilian coast south to Espírito Santo, had its range extended southwards to the latitude of Rio de Janeiro. Four distinct groups of amphipods, determined by four dominant species, were revealed by cluster analyses. The dominant species were: Ampithoe ramondi Audoin, 1826, and Erichthonius brasiliensis (Dana, 1853), both of them are epifauna tubiculous species, Leucothoe spinicarpa (Abildgaard, 1789) which is commonly which is commonly inquiline in sponges and tunicates, and Podocerus brasiliensis (Dana, 1853), which is frequently found clinging to various substrates forming aglomerates. The dry weight and volume of sponges however, did not evidence the above groups. Biological factors from the amphipod species were considered possible determinants of these groups. Only four species presented a significant sazonality: A. ramondi, L. spinicarpa, P. brasiliensis e Photis longicaudata (Bate & Westwood, 1862), all with high populations in different seasons of the year. The principal component analyses showed a positive correlation between A. ramondi and L. spinicarpa. These conspicuous species cohabited the sarne colonies, suggesting a possible association in such habitat. On the other hand, a negative correlation between E. brasiliensis and P. brasiliensis was determined. These two species have similar life habits, what suggests that competition between them may occur. Colonies with high abundance of P. brasiliensis show a low diversity, indicating a dominance of this species in relation to others.